Cheese: Importance and Introduction to Basic Technologies - Sharma Khanal, Bal Kumari; Pradhan, Monica; Bansal, Nidhi (Journal of Food Science and Technology Nepal, 2019)
Cheese is a highly nutritious fermented milk product with diverse flavour and texture. When compared to whole milk (3-4% protein and fat), it contains 30-40% protein and fat along with other minerals and fat soluble vitamins. Fewer varieties of cheese are available in Nepal compared to the European and American regions. Due to increased awareness of the health benefits of cheese and expansion of cattle farming in Nepal, the demand and supply of cheese is in increasing trend. To overcome the milk holiday in the surplus season, cheese manufacturing could be an attractive venture. By meeting the quality standards set by national and international bodies, there may be huge opportunity for exporting the cheese. However, still many dairy manufacturers are not aware about cheese production technologies and their implications. Hence, this review is aimed at providing more general information on cheese, its ingredients and steps involved in cheese making.